The Trampoline of death: Infrastructural violence in Colombia’s Putumayo frontier (2020)
Roads are usually conceived as technologies aimed at improving peoples’ economic and social welfare. As they are commonly portrayed as synonymous with mobility and with access to markets, jobs and services, their existence tends to be assumed as a major catalyst for development. This view often obscures the ways in which they affect people’s lives. This article seeks to shed light on this dimension of transport infrastructure through a historical account of a road in Colombia’s Andean-Amazon region. Infamously known as the Trampoline of death, this road has turned into an infrastructural landscape heavily invested with feelings of fear, isolation, disconnection and abandonment. Although these feelings are usually assumed as expressions of political and territorial exclusion, I will argue that, at deeper level, they reflect the violent ways in which this region has been discursively and materially included into the state. © The Author(s) 2019.